Highly reversible capacity at the surface of a lithium-rich manganese oxide: a model study using an epitaxial film system. Issue 9 (15th December 2014) - Taminato, S.; Hirayama, M.; Suzuki, K.; Yamada, N. L.; Yonemura, M.; Son, J. Y.; Kanno, R.
Abstract : The surface region of a lithium-rich manganese oxide Li2 MnO3 is intrinsically active at the electrochemical interface and exhibits a high discharge capacity over 300 mA h g −1 in the fiftieth cycle. Abstract : Epitaxial films of Li2 MnO3 were synthesized using pulsed laser deposition. A 12.6 nm film exhibited a high discharge capacity of over 300 mA h g −1 following its fiftieth cycle and better stability than 29.8 and 47.8 nm films. The surfaces of such films are intrinsically active at the electrochemical interface.